Contaminants in dietary supplements: Toxicity, doping risk, and current regulation - Zapata-Linares, J.; Gervasini, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Athletes, both amateur and professional, often resort to the consumption of nutritional supplements without professional supervision and without being aware of the risks they may entail. We conducted an exhaustive literature search to determine the most common substances found as contaminants in dietary supplements. For each substance, we analyzed its mechanism of action, clinical indication, health risk, and putative use as doping agent. In addition, we evaluated the current regulation of these supplements. Contamination of nutritional supplements (accidental or intentional), especially with steroids and stimulants, is a hazardous situation. The prolonged consumption of these products without being aware of their composition can cause serious health risks and, in the case of professional athletes, a possible sanction for doping.